Evaluation of Landslide Disaster Management in Sawahlunto - Diana Dwi Syafira; Taufika Ophiyandri; Benny Hidayat (CIVED, 2025)
Sawahlunto City had a high level of landslide vulnerability due to its hilly topography with steep slopes and clay-dominated sedimentary geological conditions. These characteristics made the area highly susceptible to prolonged heavy rainfall, which acted as the main trigger for landslides. In response, the Regional Disaster Management Agency (BPBD) of Sawahlunto implemented disaster management efforts in the pre-disaster, during-disaster, and post-disaster phases. To evaluate the effectiveness, strengths, and weaknesses of these efforts, an evaluation was conducted along with the formulation of alternative strategies for landslide disaster risk reduction. This study employed a qualitative approach, based on interviews with 26 respondents, including relevant agency representatives and affected community members. A SWOT analysis was used to evaluate disaster management activities by identifying internal (strengths and weaknesses) and external (opportunities and threats) factors. The data were analyzed using thematic analysis to identify key themes based on similarities in the respondents’ statements. The results indicated several strengths, including disaster education programs, the Sitaruna Darling initiative, hazard warning signs, risk assessment documents, community forums, and inter-agency collaboration. Weaknesses included limited structural mitigation, poor drainage management, unregulated development, uneven distribution of disaster education, gaps in the formation of Disaster Resilient Villages, damaged early warning systems, and limited financial and human resources of BPBD. Opportunities involved community interest in disaster education, village fund allocation, technological utilization, a strong local cooperation culture, and potential support from BNPB and local parliament programs Major threats included prolonged high-intensity rainfall, unstable topographic and geological conditions prone to landslides, and low public understanding of landslide disaster risks. The recommended strategies involved enhancing inter-agency synergy, optimizing structural mitigation, strengthening regulations, ensuring equal access to disaster education, developing Sitaruna Darling innovations, improving early warning systems, and utilizing BNPB grants for recovery efforts.